Symbolic Ecology in "Aku, Hutan Jati, dan Indonesia": Ecolinguistics Perspective - Siregar, Usmala Dewi; Maulina, Intan; Nasution, Meisa Fitri (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2024)
This study will discuss the phenomenon of symbolic ecology to describe the diversity of objects found in the poetry "Aku, Hutan jati, dan Indonesia" as well as to analyze the symbolic meaning and philosophy for each object deemed to imply the relationship between the diversity of objects and the environment in Indonesia. This study aimed to provide representations of the symbolic ecological phenomena found in the poem The Aku, Hutan jati, dan Indonesia" and uncover the philosophy of symbolic meanings about the environment and Indonesia's manner of viewing the symbols. This study analyzed the poem "Aku, Hutan jati, dan Indonesia" by Jacinta Kurniasih. This study used an ecolinguistic design, in which the data analysis process used an ecolinguistic framework, and the data interpretation used a cultural semiotics framework. The results of this study indicated that the poet's environmental concern was expressed through the adoption of macrocosm objects and flora. The results of this study proved that language can be used to inspire by conveying humanistic messages for protecting the ecosystems, which have provided benefits to human life and prevented natural disasters from happening. It is also suggested that people should care for fellow human beings and the surrounding nature that has contributed to the continuation of human life.